Germplasm Sources, Genetic Richness, and Population Differentiation of Modern Chinese Soybean Cultivars Based on Pedigree Integrated With Genomic-Marker Analysis - Li, Chunyan; Wang, Wubin; Pan, Yongpeng; Liu, Fangdong; He, Jianbo; Liu, Chuanxiang; Cao, Jiqiu; Zhang, Xiaoyan; Zhao, Jinming; Gai, Junyi (Frontiers in Plant Science, 2022)
Soybean is a native crop in China with ~5000 years. The 560 cultivars released in 2006-2015, commercialized with seeds available publicly, were collected (designated modern Chinese soybean cultivars, MCSCs), as a part of 2,371 ones released during ~100 years’ breeding history. The MCSCs with their parental pedigrees were gathered, including 279, 155 and 126 cultivars from Northeast and Northwest China (NNC), Huang-Huai-Hai Valleys (HHH) and Southern China (SC), respectively. The MCSCs were tested in field, genotyped with sequencing and analyzed for their germplasm sources, genetic richness and population differentiation based on pedigree integrated with genomic-marker analysis. The main results were as follows: (i) The MCSCs covering 12 of global 13 MGs (maturity groups) showing different ecoregions with different cropping systems caused their different MG constitutions. (ii) Parental pedigree analysis showed 718 immediate parents and 604 terminal ancestors involved in MCSCs, from which 41 core-terminal ancestors identified. (iii) NNC was richer in allele number and specific present/deficient alleles, and genetically distant from HHH and SC. (iv) The geographic grouping of MCSCs was partially consistent with marker-based clustering, indicating multiple genetic background in three eco-subpopulations. (v) Eleven major core-terminal ancestor-derived families were identified, including four derived from ancestors in NNC, four from HHH and three from SC, containing 463 (82.68%) MCSCs with some cross-distribution among ecoregions. (vi) CGS (coefficient of genetic similarity) calculated from genomic markers showed more precise than COP (coefficient of parentage) using pedigree information in evaluating genetic relationship/differentiation. Overall, through pedigree and genomic-marker analyses, the germplasm constitutions of the three eco-subpopulations were relatively self-sufficient, germplasm exchange is seriously required for further improvement.